Comparative efficacy of chronic lymphocytic leukemia treatment with or without rituximab - E. A. Zenkova; Б. Е. Kugushev; E. R. Vasilieva (Онкогематология, 2019)
Background. Monoclonal antibodies are modern drugs for the treatment of chronic lymphocytic leukemia.The objective is a comparative study of the monoclonal antibody rituximab efficacy when added to cyclophosphamide + fludarabine (RFC versus FC regimen) in the treatment of chronic lymphocytic leukemia.Materials and methods. A retrospective study was conducted in Clinical Medical Unit No. 1 of Perm. In total, the response to treatment was analyzed in 22patients (11 patients in each group (FC and RFC therapy)).Results. Adding rituximab to the FC treatment regimen reduced the number of lymphocytes below 4 х 10 9/L after the 1st course, while maintaining the neutrophil level above 1.5 х 109/L, the absence of anemia (hemoglobin level >130 g/L) and thrombocytopenia (platelet count > 100 х 109/L). An additional assessment of creatinine and uric acid levels showed the absence of tumor lysis syndrome during RFC therapy.Conclusion. The addition of rituximab (RFC therapy) to cyclophosphamide + fludarabine (FC therapy) provides a more rapid therapy response without adverse toxic effects such as impact on bone marrow functional activity and tumor lysis syndrome.